The Effects of Workplace Environment, Compensation, and Learning Organization on Employee’s Innovative Work Behavior - Ula, Ahmad Mushonniful; Azzuhri, Misbahuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
In this era, innovation is needed in running an organization in order to survive and be sus-tainable in the future. The objective of this research is to identify and elucidate the effects of workplace environment, compensation, and learning organization on innovative work behavior. In this exploratory study, the causal relationships of those variables were corrob-orated via hypothesis testing. Using census sampling, all 45 employees of PT BPR Mentari Terang, a rural bank in Tuban, were selected as samples. The data was harvested through validity and reliability-tested Likert questionnaires and was analyzed descriptively and statistically using multiple linear regression in SPSS version 26. This study finds that work-place environment significantly influences employee’s innovative work behavior, compen-sation does not affect the innovative work behavior, and that organizational learning sig-nificantly affects the innovative work behavior. Therefore, companies are expected to continue to improve the conditions of the office work environment, hold company tours or recreation involving all employees, entertainment, and other things that can support em-ployee well-being, increase interest in learning so that employees feel interested and happy in carrying out the tasks given by the company.